Identifikasi Komentar Negatif Berbahasa Indonesia Pada Instagram Dengan Metode K-Means - Yoannes Romando Sipayung; Reny Sulistyowati (Universitas Ngudi Waluyo, 2019)
Comments given by users or people on social media such as Instagram are varied, some are positive or negative. In terms of netizens, there is nothing wrong when you want to comment or pour out your heart. In Indonesia, denying netizens comments related to negativity, agreeing to agree with the law and the police. This research will help people who want to send comments that they make so as not to contain negative content so they can avoid cyber crime. The method used in supporting this research is the K-Mean method, to determine whether the comments entered are positive or negative. In this study, the data used were 40 comments that were used as research objects.Â Keywords:Â Negative Comments, Instagram, K-Means